What influences the diffusion of grassroots innovations for sustainability? Investigating community currency niches. Issue 1 (2nd January 2016) - Seyfang, Gill; Longhurst, Noel
ABSTRACT: Community action for sustainability is a promising site of socio-technical innovation. Here we test the applicability of co-evolutionary niche theories of innovation diffusion (strategic niche management, SNM) to the context of 'grassroots innovations' (GIs). We present new empirical findings from an international study of 12 community currency niches (such as Local Exchange Trading Schemes, time banks, and local currencies). These are parallel systems of exchange, designed to operate alongside mainstream money, meeting additional sustainability needs. Our findings confirm SNM predictions that niche-level activity correlates with diffusion success, but we highlight additional or confounding factors, and how niche theories might be adapted to better fit civil society innovations. In so doing, we develop a model of GI niche diffusion which extends existing work and tailors it to this specific context. The paper concludes with a series of theoretically informed recommendations for practitioners and policy-makers to support the development and potential of GIs.